Distributions of the Pelagic Holothurian Pelagothuria in the Central Pacific Ocean as Observed by Remotely-Operated Vehicle Surveys - Selig, Gina M.; Netburn, Amanda N.; Malik, Mashkoor (Frontiers in Marine Science, 2019)
Pelagothuria is the only known genus of holothurian that is holopelagic. There is thought to be only one species, Pelagothuria natatrix, and little is known about their abundance and distribution throughout the global ocean. Most documented observations of Pelagothuria are in the Eastern Tropical Pacific, an ecoregion with a shallow thermocline and low dissolved oxygen concentrations, suggesting that Pelagothuria may be associated with oxygen minimum zone regions. During the spring 2017 NOAA Ship Okeanos Explorer Mountains in the Deep Expedition, scientists onboard the ship and participating through telepresence noted seeing an exceptional number of Pelagothuria during ROV dives conducted at sites along a transit from Pago Pago, American Samoa to Honolulu, Hawaii. Video from all dives was later reviewed using the video replay and annotation tool SeaTube and Pelagothuria were seen at 9 of the 12 ROV dive sites explored. A total of 97 occurrences of Pelagothuria were observed in depths ranging from 196 to 4440 m, temperatures of 1.3 to 15.4 °C, salinities of 34.5 to 35.2, and oxygen concentrations of 0.17 to 3.77 mg L-1. The vertical distribution of Pelagothuria averaged 865 m depth, and their observations occurred at means of 5.24 °C, 34.56, 1.71 mg L-1 for temperature, salinity and dissolved oxygen, respectively. Results suggest that the horizontal distributions of Pelagothuria may extend to the Equatorial Pacific region, and the relatively high occurrence of Pelagothuria in oxygen minimum zones indicates they may be particularly hypoxia-tolerant. In the absence of repeat or long-term observations, it is not possible to discern whether this phenomenon was a bloom or a persistent feature of the area. The recent strong El Niño event and anomalously warm conditions throughout much of the Pacific could have provided conditions favorable to a Pelagothuria bloom, however the high abundances of the organism seen on a nearby 2015 expedition suggest that this may be a persistent feature. The water column in this region has never before been explored with ROVs, and this study demonstrated use of an archived and publicly-accessible exploratory dataset to make novel discoveries.